1973
DOI: 10.1159/000169650
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Cardiac Sympathetics on Left Ventricular Dynamics during Tachycardia

Abstract: Increasing heart rate by atrial pacing in conscious, resting dogs resulted in declines in stroke volume (-0.40 ml/beat-kg/100 beats/min; p < 0.001), and left ventricular transverse internal diameter at end-diastole (-3.40 mm/100 beats/min; p < 0.001) and end-systole (-2.14 mm/100 beats/min; p < 0.001). When pacing was repeated following β-adrenergic blockade, stroke volume declined slightly more than had occurred during the control response. The decrease in end-diastolic diameter was -2.13 mm/100 beats/min whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1979
1979

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We have also shown that elevation in heart rate at rest, either through electrical pacing (Bishop & Horwitz, 1974), vagal blockade (Bishop & Horwitz, 1971) or infusion of isoprenaline decreases left ventricular end-diastolic diameter. We have shown that left ventricular internal transverse diameter measured with a sonocardiometer is an accurate index of left ventricular volume in normal dogs (Bishop, Horwitz, Stone, Stegall & Engelken, 1969;Bishop & Horwitz, 1970).…”
Section: Changes In Cardiac Outputmentioning
confidence: 75%
See 1 more Smart Citation
“…We have also shown that elevation in heart rate at rest, either through electrical pacing (Bishop & Horwitz, 1974), vagal blockade (Bishop & Horwitz, 1971) or infusion of isoprenaline decreases left ventricular end-diastolic diameter. We have shown that left ventricular internal transverse diameter measured with a sonocardiometer is an accurate index of left ventricular volume in normal dogs (Bishop, Horwitz, Stone, Stegall & Engelken, 1969;Bishop & Horwitz, 1970).…”
Section: Changes In Cardiac Outputmentioning
confidence: 75%
“…Therefore, afterload changes were not relevant to our analysis under these experimental conditions. However, acute afterload changes in the conscious dog at rest can limit cardiac output (O'Rourke, Pegram & Bishop, 1974).…”
Section: Discussionmentioning
confidence: 99%